Pharmacokinetic analysis and structural optimization of inophyllamine-I to forecast as a possible drug candidate - Chinta Sudheer Kumar; M. Lakshmi Narasu; C. Ravinder Singh (Elsevier, 2023)
Background: : A novel bioactive compound 2-ethyl-1, 2, 3, 4-tetrahydro-N-(methoxy(methylperoxy)-3-acetate, methyl)-3, 4- bis(methylperoxy)naphthalen-1-amine, named inophyllamine-1(INM-I) was the isolate of Callophyllum inophyllum, and also a potent antioxidant.This compound significantly reduced the B(a)P-induced lung tumor volume, and its curative effect was confirmed by histology of lung tissue. Computational research was conducted for the first time to elucidate the structural and molecular dynamic behavior of INM-1 at the therapeutic targets of cancer. Methodologies: : This study aims to elucidate the 3D structure of inophyllamine-1 and geometry optimization at the Hartree-Fock level 3-21 G and B3LYP functional basis set to improve structures by DFT (Density function theory) calculations. For the pharmacokinetic properties of INM-1, an ADMET study was conducted using SWISS ADME and pkCSM online servers. Molecular docking was performed to evaluate the interactions of INM-1 with Bax, Bcl2, p53, and PlK-1 receptor active sites. A dynamic molecular study was conducted for the PlK-1, and INM-1 best dock posesto understand the dynamic behavior for 100 ns. Results: : The structural and pharmacokinetic properties of INM-1 exhibit bioavailability and drug-likeness characteristics and promote cytotoxicity. Themolecular docking results depict the INM-1 as a potential inhibitor against the therapeutic targets Bax, Bcl2, p53, and Polo-like-kinase-1(PlK-1) with minimum binding energies -6.0, -6.4, -6.1, and -7.3 kcal/mol. The INM-1 possesses a strong binding affinity towards the PlK-1 receptor and exhibits a stable complex for 100 ns molecular dynamics simulation time. Conclusions: : The computational studies by molecular docking elucidated the interactions between INM-1 and the catalytic residues of PlK-1, as well as the other cancer therapeutic targets, Bax, Bcl2, and p53 active sites. The outcomes of molecular dynamic simulations strongly imply that INM-1 may play a significant role in suppressing cancers. This study concludes that the Callophyllum inophyllum-derived INM-1 has the potential to be an effective drug candidate.